THE EVOLUTION OF STATE AID IN ROMANIA. ANALYSIS OF THE AUTOMOTIVE SECTOR 2007-2015 - George STEFAN; Raluca Andreea POPA; Alina ARSANI (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2016)
This study, according to our knowledge is among the few ones dealing with the analysis of state aid impact and of the way it was used at national level. Firstly, the goal of our study is to analyze the evolution of state aid in Romania, the impact on regional development, on creating jobs and value added. Secondly it is intented to see the contribution of automotive sector which received the highest amount of state aid to the trade balance from the current account between 2008-2015. Automotive sector is a key sector for the development of Romanian economy in the last 10 years for the manufacturing and assembly of cars and for companies producing equipment or auto parts. The paper is structured in seven parts which deal with topics like the state aid in the European Union and Romania, state aid schemes and funded sectors in Romania, sectorial and geographical distribution of the state aid, the analysis of the automotive sector for Romania.